Sporadic and thermospheric enhanced sodium layers observed by a lidar chain over China. Issue 10 (3rd October 2013) - Dou, X. K.; Qiu, S. C.; Xue, X. H.; Chen, T. D.; Ning, B. Q.
<x xml:space="preserve">Abstract</x> [1] We report the statistical features of sporadic sodium layers (SSLs) and the thermospheric enhanced sodium layers (TeSLs) observed by a lidar chain located at Beijing (40.2°N, 116.2°E), Hefei (31.8°N, 117.3°E), Wuhan (30.5°N, 114.4°E), and Haikou (19.5°N, 109.1°E). The average SSL occurrence rate was approximately 46.0, 12.3, 13.8, and 15.0 h per SSL at Beijing, Hefei, Wuhan, and Haikou, respectively. However, the TeSLs occurred relatively infrequently and were more likely to appear at low and high latitudinal sites. Both the SSLs and TeSLs at four lidar sites showed evident summer enhancements and correlated well with Es (foEs>4 MHz). The coobservations of SSLs at three lidar site pairs, i.e., Hefei‐Beijing, Hefei‐Wuhan, and Hefei‐Beijing, indicated that a large‐scale SSL extended horizontally for at least a few hundred kilometers and exhibited a tidal‐induced modulation. Moreover, the SSLs were better correlated for the Hefei‐Wuhan and Hefei‐Haikou pairs than the Hefei‐Beijing pair, which suggested a difference in the dynamical/chemical process in mesosphere and lower thermosphere (MLT) between the Beijing site and the other sites.